Quadrivalent HPV vaccine effectiveness against high‐grade cervical lesions by age at vaccination: A population‐based study - Herweijer, Eva (Int J Cancer, 2016)
Human papillomavirus (HPV) types 16/18, included in HPV vaccines, contribute to the majority of cervical cancer, and a substantial proportion of cervical intraepithelial neoplasia (CIN) grades 2/3 or worse (CIN2+/CIN3+) including adenocarcinoma in situ or worse. The aim of this study was to quantify the effect of quadrivalent HPV (qHPV) vaccination on incidence of CIN2+ and CIN3+. A nationwide cohort of girls and young women resident in Sweden 2006–2013 and aged 13–29 (n = 1,333,691) was followed for vaccination and histologically confirmed high‐grade cervical lesions. Data were collected using the Swedish nationwide healthcare registers. Poisson regression was used to calculate incidence rate ratios (IRRs) and vaccine effectiveness [(1‐IRR)x100%] comparing fully vaccinated with unvaccinated individuals. IRRs were adjusted for attained age and parental education, and stratified on vaccination initiation age. Effectiveness against CIN2+ was 75% (IRR = 0.25, 95%CI = 0.18–0.35) for those initiating vaccination before age 17, and 46% (IRR = 0.54, 95%CI = 0.46–0.64) and 22% (IRR = 0.78, 95%CI = 0.65–0.93) for those initiating vaccination at ages 17–19, and at ages 20–29, respectively. Vaccine effectiveness against CIN3+ was similar to vaccine effectiveness against CIN2+. Results were robust for both women participating to the organized screening program and for women at prescreening ages. We show high effectiveness of qHPV vaccination on CIN2+ and CIN3+ lesions, with greater effectiveness observed in girls younger at vaccination initiation. Continued monitoring of impact of HPV vaccination in the population is needed in order to evaluate both long‐term vaccine effectiveness and to evaluate whether the vaccination program achieves anticipated effects in prevention of invasive cervical cancer.